A Negotiator's Guide to Regional Trade Agreements : Considerations from an East Asian Perspective - Baller, Silja (World Bank, Washington, DC, 2012)
This report maps out the evolving architecture of regional trade agreements concluded by the major trading countries and the countries of East Asia. The report first looks at a group of systemic issues - preferential rules of origin, dispute settlement and trade remedies - and subsequently turns to substantial provisions on market access, intellectual property rights, and competition policy. It also briefly examines the nascent stage of environment and labor clauses. As most favored nations (MFN) tariffs continue to fall, tariff reductions are starting to play a less important role in negotiations with the focus increasingly shifting to regulatory issues. Another notable feature of regional trade agreements (RTAs) negotiated today is that their geographical reach has begun to extend far beyond the traditional close proximity of AFTA, EU, or NAFTA - often making the term "RTA" a misnomer. The goal of this report is to establish patterns and directions across a range of issues covered in RTAs today which are relevant for East Asian policy makers. The report hence looks at pertinent systemic and substantial provisions currently included in RTAs: the first half includes chapters on rules of origin, dispute settlement, and trade remedies (all of these are systemic and pin down the credibility of the concessions made: the extent of enforcement, requirements for qualification, and the ease by which a party may opt out); the second half of this report investigates market access provisions and different sets of rules concerning regulatory issues related to intellectual property rights, competition policy, the environment, and labor. Individual provisions from prominent RTAs concluded between East Asian countries and across the rest of the world will be used throughout for illustrative purposes.